Parents' participation in physical activity predicts maintenance of some, but not all, types of physical activity in offspring during early adolescence: A prospective longitudinal study - Jennifer Brunet; Jeffrey Gaudet; Erin K. Wing; Mathieu Bélanger (Elsevier, 2019)
Purpose: We aimed to examine the longitudinal associations between parents' and youth's participation in physical activity (PA). Methods: One hundred and ninety youth completed self-administered questionnaires 3 times per year from 2011 to 2015, and their parents completed an interviewer-administered questionnaire during a telephone interview once in 2011-2012. Data on youth's and parents' activities were classified as interdependent or coactive/independent. Results: Youth with one or both parents who participated in interdependent activities were more likely to maintain participation in interdependent activities (hazard ratio (HR) = 3.63; 95% confidence interval (CI) = 1.30-10.17). Youth's sustained participation in coactive/independent activities was not associated with parents' participation in coactive/independent activities (HR = 0.97; 95%CI = 0.46-2.06). Conclusion: Longitudinal associations between parents' and youth's participation in PA differed across type of PA. Encouraging parents' participation in interdependent activities may promote sustained participation in interdependent activities in youth. Keywords: Longitudinal, Maintenance, Parental behavior, Physical activity, Sports, Youth